Communication and knowledge of public Social Services. Dissemination of Municipal Social Services in the Comunidad of Madrid - Baltar Moreno, Adolfo (Cuadernos de Trabajo Social, 2014)
The article analyses the publicizing of primary care social services in the Municipality (Comunidad) of Madrid through the local Administrations, the institutions that produce and manage these public services, as broadcasters or principal producers of this communication process. It is based on the hypothesis that the model of publicity used by the local Administrations to promote their social services determines the level of public knowledge of this social protection system and influences people’s access to the system. The research presents a diagnosis based on the observation of the principal factors that determine the construction of the image of municipal social services: strategies, content, advertising, marketing, product placements and obstacles. The conclusions lead us to propose the need to carry out a global dissemination of information about public social services as a system, supplementary to the efforts of remaining public Administrations concerned, which is not happening at present.